PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT UNTUK MEREMEDIASI MISKONSEPSI PESERTA DIDIK PADA MATERI GLBB - yarso, Julina; Sitompul, Stepanus Sahala; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to determine the effectiveness of the use of the Numbered Heads Together (NHT) type cooperative leaning model in reducing student’s  misconception on irregularly moving straight material in SMA Negeri 1 Paloh. The form of research used was pre-experimantal design with on group pretest-postest design. The study used a satuated sample of class X IPA which consists of 34 student’s. The result of study obtained a decrease in the percentage of students who misconceptions each concept with an average of 66% and a decrease in the percentage of the number of misconceptions per students with an average 61,6%. Based on the distribution of the number of students who experience misconceptions during the pretest and postest an average difference of 39,14%. The results of Mc Nemar significance test on df = 1 and α= 5% showed > , were equal to 92,25 > 3,84. There was a conceptual change on the students significantly. The Decreasing Quantity Students that Misconception (DQM) Numbered Heads Together model in remediating misconception were 39,44% (medium category). The results of this research were expected to be used as the development material of Numbered Heads Together in remediation learning about the irregularly moving straight material. Keywords: Misconseption, Numbered Heads Together (NHT) type cooperative leaning model, remediation